Tomato seed oil attenuates hyperlipidemia and modulates gut microbiota in C57BL/6J mice. Issue 5 (1st May 2020) - He, Wen-Sen; Li, Lingling; Rui, Jiaxin; Li, Junjie; Sun, Yuying; Cui, Dandan; Xu, Bin
Abstract : TSO can significantly improve fatty acid metabolism and cholesterol metabolism, thereby inhibiting obesity and hypercholesterolemia. TSO can favorably modulate the gut microbiota. Abstract : In this study we aimed to investigate the role of tomato seed oil (TSO) in the alleviation of hyperlipidemia and the regulation of gut microbiota in C57BL/6J mice. Mice were divided into the following four diet-based groups: low-fat diet (LF, n = 8), high-fat diet (HF, n = 6), HF diet with TSO replacing one-third of lard (TL, n = 8), and HF diet with TSO replacing two-thirds of lard (TH, n = 8). The results showed that TH significantly reduced weight gain, relative adipose tissue weights, plasma cholesterol, triacylglycerol, low-density lipoprotein cholesterol (LDL-C), ratio of LDL-C to high-density lipoprotein cholesterol (HDL-C), hepatic cholesterol, and total fatty acids, and markedly increased plasma HDL-C. TSO supplementation also dose-dependently increased fecal cholesterol excretion and reduced fecal total fatty acids. This was accompanied by upregulation of the gene expression of hepatic PPAR α, ACADL, CYP7A1, LXR α, ABCA1, and SR-B1. Metagenomic analyses demonstrated that TSO tended to reduce the Firmicutes / Bacteroidetes ratio, significantly increased the relative abundance of the genus Lactobacillus, and reduced the relative abundance of the genera Rikenella, Enterorhabdus, unclassified_o_Clostridiales and Ruminococcaceae_UCG-009 . These results proved that TSO was effective in attenuating hyperlipidemia in C57BL/6J mice by enhancing fatty acid β-oxidation, reducing cholesterol absorption, promoting cholesterol efflux, and favorably modulating the gut microbiota.